2021
DOI: 10.1039/d1ra07375c
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive platform for DNA detection based on organic electrochemical transistor and nucleic acid self-assembly signal amplification

Abstract: A new method has been developed for DNA detection by integrating hybridization chain reaction signal amplification with organic electrochemical transistor device for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In order to prepare the conductive film, DMSO (5%, v/v) and MPTMS (5%, v/v) were added into the PEDOT:PSS solution to improve the conductivity, stability and bio-affinity during the anneal process. 13,40 The mixed PEDOT:PSS solution was spin-coated on the patterned photoresist with a speed of 3000 rpm for 30 s and then annealed on a hot plate at 100 °C for 2 h under a high-purity N 2 environment in a glovebox. The condition of pure nitrogen prevents oxidative denaturation of PEDOT:PSS during heating and prevents degradation of electrical conductivity.…”
Section: Methodsmentioning
confidence: 99%
“…In order to prepare the conductive film, DMSO (5%, v/v) and MPTMS (5%, v/v) were added into the PEDOT:PSS solution to improve the conductivity, stability and bio-affinity during the anneal process. 13,40 The mixed PEDOT:PSS solution was spin-coated on the patterned photoresist with a speed of 3000 rpm for 30 s and then annealed on a hot plate at 100 °C for 2 h under a high-purity N 2 environment in a glovebox. The condition of pure nitrogen prevents oxidative denaturation of PEDOT:PSS during heating and prevents degradation of electrical conductivity.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, R. He et al have reported the OECT device as a DNA biosensor with the interacted hybridization chain reaction for signal amplification at low cost and easier fabrication. [389] Here, the Au NPs were electrochemically deposited on the Au gate electrode, and negatively charged double-stranded DNA was connected to the gate electrode by hybridization (Figure 11c 1 ). The state and length change of DNA could increase the effective gate voltage offset of the OECT device up to 35 mV (Figure 11c 2 ).…”
Section: Microelectronicsmentioning
confidence: 99%
“…Reproduced with permission. [ 389 ] Copyright 2021, The Royal Society of Chemistry. d 1 ) A TEM image of lamellar Mo 2 C nanosheets, d 2 ) cyclic voltametric (CV) curves of the assembled Mo 2 C/activated carbon sodium‐ion capacitors (SIC) at different scan rates, and d 3 ) cyclic stability of SIC at a current density of 1 A g −1 .…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…An emerging technology that holds broad prospects for overcoming the abovementioned limitations is the organic electrochemical transistor (OECT), an ideal multifunction device that is suitable for both biochemical and bioelectrical sensing. Since it was first proposed by Wrighton and co-workers in 1984, [27] OECTs of different types have demonstrated superb abilities in chemical sensing, [28][29][30][31][32][33][34] cell culture and action potential recording, [35][36][37][38][39][40] and health monitoring. [41][42][43][44][45] OECTs exhibit a unique set of advantages for various sensing applications, such as: 1) a biocompatible organic (semi)conductor in the OECT channel making it an ideal platform to interface with biological systems; [46][47][48] 2) fabrication of OECTs is compatible with various low-temperature processing techniques, from low-cost, high-throughput printing methods to conventional photolithography; [49][50][51][52] 3) benefiting from the signal conversion and amplification capabilities of OECTs, high current modulation and fast response can be achieved leading to excellent sensing performance; [53][54][55] 4) operation of OECTs in aqueous electrolyte solutions is suitable for working in complex physiological environments; [56] 5) high compatibility of OECTs with traditional microelectronic integration techniques enables the fabrication of high density sensing arrays for mapping purposes [57][58][59] as well as fabrication of OECT-based microfluidics for multiple analyte detection; [60][61]…”
Section: Introductionmentioning
confidence: 99%